A systematic scoping review of dental anomalies associated with cleft lip and palate patients (Bangladesh Journal of Medical Science, 2023)
Objective: The aim of this systematic scoping review is to explore the data regarding dental anomalies related to oral clefts.Methodology: A systematic literature search was conducted by two independent reviewers focusing on all types of dental anomalies in cleft lip and palate (CLP) patients. A search string was developed and searched through the PubMed and Scopus database to identify the relevant articles. Identification for additional relevant studies was performed through a manual search of the reference lists of the selected articles. Each selected article was then qualitatively analyzed using Atlas’s software.Results and Discussion: Eight studies that stated the prevalence of dental anomalies in CLP patients were included and no language restrictions were imposed. Despite lack of standardization in reporting,dental anomalies regarding the tooth form or shape, number of teeth, structural disturbances, and eruption sequence were noted.Conclusion: Among cleft group, agenesis was found as the most common dental anomaly with lateral incisor being most commonly involved.The use of standardized classifications and protocols to report cleft types and dental anomalies will be beneficial for clinicians and researchers for identification and better management of the conditions.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 22-31